Une approche multidisciplinaire de la fabrique des paysages dans la longue durée dans les forêts de Blois, Russy, Boulogne et Chambord (Loir-et-Cher) - Aude Crozet; Clément Laplaige; Xavier Rodier (Projets de Paysage)
Forests are environments favourable to the conservation of anthropogenic vestiges because the action of erosion is less marked in forests than in open areas. The archaeological work conducted in these forests focuses on all kinds of vestiges preserved by the cover of vegetation as well as human forestry activities (Dupouey et al., 2007). These two approaches were used within the framework of the SOLiDAR programme, namely thanks to the LiDAR remote detection survey conducted during the winter of 2015, the first findings of which are presented here. The area studied includes the Chambord national estate and the state-owned forests of Boulogne, Russy and Blois, representing a woodland area of close to 25 000 hectares. In addition to pedestrian surveys conducted over a period of 15 years, the LiDAR survey made it possible to identify vestiges which are invisible to the naked eye and which concern the former exploitation of the forest as well as prior human settlements. This diachronic approach, combining sources widely used by archaeologists (archaeological digs and excavations, archives, geomorphological and ecological surveys) and LiDAR technology makes it possible to use regressive analysis in the long-term study of forestry landscapes.